Pengembangan Perangkat Pembelajaran IPA Terpadu Berbasis Salingtemas dan Inkuiri Terbimbing untuk Membentuk Pemahaman Terintegrasi Peserta Didik SMP - Laila Khusnah; Ibrohim Ibrohim; Abdul Ghofur (Jurnal Pendidikan Sains, 2017)
Abstract: This research aims at (1) producing the science instructional materials for SMP based on salingtemas and guided inquiry to build the integrated understanding; (2) discovering the validity and reliability levels of the instructional materials, namely Syllabus, Lesson Plans (RPP), Assessment Instruments, and Students’ Worksheet (LKPD). This research used development research design 4D model suggested by Thiagarajan and limited only to the development level. The developed instructional materials are validated by the expert of instructional materials, the expert in the subject, the science teacher, then, the learning device tested on eight graders of SMPN 2 Jember to discover the readability of LKPD. The validation test result from all validators showed that the science instructional materials based on the salingtemas and guided inquiry have categorized as valid. The readability evaluative result showed that the LKPD can be used in learning process, and the totality the science instructional materials based on salingtemas and guided inquiry effectively used on learning process. Key Words: instructional materials, integrated understanding, salingtemas, guided inquiry